Fixation stability dictates the differentiation pathway of periosteal progenitor cells in fracture repair. Issue 7 (13th May 2015) - Hagiwara, Yusuke; Dyment, Nathaniel A.; Jiang, Xi; Jiang Ping, Huang; Ackert‐Bicknell, Cheryl; Adams, Douglas J.; Rowe, David W.
ABSTRACT This study compared fracture repair stabilized by intramedullary pin (IMP) or external fixation (EF) in GFP reporter mice. A modified IMP was used as control while EF utilized six needles inserted transversely through the tibia and into a segment of a syringe barrel. X‐rays taken at days 0, 14, and 35 showed that IMP resulted in significant three‐dimensional deformity with a large callus while EF showed minimal deformity and callus formation. Cryohistological analysis of IMP at day 14 confirmed a large ColX‐RFPchry+ callus surrounded by woven bone (Col3.6‐GFPcyan) and TRAP+ osteoclasts with mature bone (hOC‐GFPtpz) at the base. By day 35, cartilaginous components had been resorbed and an outer cortical shell (OCS) showed evidence of inward modeling. In contrast, the EF at day 14 showed no evidence of cartilage formation. Instead, periosteal‐derived osteoblasts (Col3.6‐GFPcyan) entered the fracture cleft and formed woven bone that spanned the marrow space. By day 35, mature bone had formed that was contiguous with the opposing cortical bone. Fracture site stability greatly affects the cellular response during repair and must be considered in the preclinical models that test therapies for improving fracture healing. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:948–956, 2015.